Neutron beam line for TOF measurements at the Spanish National Accelerator Lab (CNA) - Macías Miguel; Fernández Begoña; Praena Javier (EPJ Web of Conferences, 2020)
A few years ago, the Spanish National Accelerator Lab (CNA) developed the first accelerator-based neutron facility in Spain called HiSPANoS (HiSPAlis Neutron Source). The first applications of the line were related to integral measurements applied to nuclear astrophysics, dosimetry and single event effects produced by neutrons in electronic devices. The successful of HiSPANoS pushed the enhancement of the facility. In collaboration with the NEC® Company, two devices were designed for pulsing ion beams (Chopper) and for compressing in time (Buncher) the pulsed beams. The Chopper-Buncher system has been already installed and commissioned. Proton and deuteron beams are delivered with repetition rates from 62.5 kHz to 2 MHz and 1 ns pulse width. In addition, a new line of the 3 MV Tandem Pelletron accelerator was designed for neutron time-of-flight (TOF) experiments. Conventional devices and a dedicated Pick-Up for timing measurements form the new line. In order to check the performance of the whole TOF system, we have carried out the measurement of the neutron spectrum produced by 7Li(p,n)7Be reaction at Ep = 1912 keV. Such spectrum has been measured by the TOF technique few times and it can be considered a standard neutron field, in particular in nuclear astrophysics. The first result of such experiment performed at CNA is shown in some detail. The excellent performance of the accelerator, the Chopper-Buncher system and the acquisition system allow us to offer the TOF line at HiSPANoS-CNA to the neutron community.